A study on cognitive trajectory changes and predictive factors in middle-aged and older adults individuals with dual sensory impairment based on the health social determinants model - Ma, Li; Pang, Jiaxue; Liu, Qiankun; Li, Pengyao; Huang, Juju; Xu, Yang; Xie, Hui (Frontiers in Public Health, 2024)
AimThis study aims to explore the cognitive trajectory changes in middle-aged and older adults individuals with dual sensory impairment (simultaneous visual and hearing impairment) and to identify the predictors of different trajectory changes.MethodsBased on the longitudinal data from the China Health and Retirement Longitudinal Study (CHARLS) from 2013 to 2020, data from 2,369 middle-aged and older adults individuals with dual sensory impairment were selected. A latent variable growth mixture model was constructed to analyze the cognitive function development trajectories in this population and to identify their predictive factors.ResultsThe cognitive function development trajectories in the middle-aged and older adults population can be categorized into three types: high cognitive level stable group, low cognitive level slowly declining group, and moderate cognitive level rapidly declining group. Logistic regression analysis showed that age (OR 30.544; 95% CI 9.35–99.754; p < 0.001), sleep duration (OR 0.559; 95% CI 0.343–0.909; p < 0.005), education (OR 0.009; 95% CI 0.003–0.025; p < 0.001), marital status (OR 2.122; 95% CI 1.457–3.090; p < 0.001), social participation (OR 0.499; 95% CI 0.379–0.658; p < 0.001), place of residence (OR 1.471; 95% CI 1.089–1.988; p < 0.001), and medical insurance (OR 0.353; 95% CI 0.169–0.736; p < 0.005) are predictive factors for cognitive function trajectories in this population.ConclusionThere is group heterogeneity in the cognitive function development trajectories among middle-aged and older adults individuals with dual sensory impairment. Factors such as less than 4 h of nighttime sleep, low social participation, alcohol consumption, and lack of medical insurance are modifiable risk factors for cognitive decline in this population. Preventive strategies should be formulated accordingly, especially for vulnerable groups, including older rural residents and those with lower educational attainment, to prevent cognitive function deterioration in middle-aged and older adults individuals with dual sensory impairment.